ANALISIS KEMUDAHAN AKSES KREDIT BANK MELALUI SERTIFIKAT TANAH ELEKTRONIK: PELUANG DAN TANTANGAN BAGI PEMILIK USAHA MIKRO DAN KECIL - Loso Judijanto (BORJUIS: JURNAL OF ECONOMY, 2025)
The transformation of land services through the implementation of electronic land certificates in Indonesia opens up significant opportunities for improving access to bank credit for micro and small enterprises (MSEs). This study aims to analyse the opportunities and challenges of utilising electronic land certificates as collateral for MSE loans using a literature review method. Data were obtained from government regulations, banking provisions, academic studies, official reports, and relevant news articles. The analysis results indicate that the digitisation of land certificates offers several opportunities, including enhanced legal certainty, accelerated verification processes, administrative efficiency, strengthened financial inclusion, and the creation of more competitive credit products. However, its implementation also faces real challenges such as limited digital literacy, uneven technological infrastructure, data security risks, public scepticism towards digital documents, and the unpreparedness of some banking institutions. This study emphasises that the successful utilisation of electronic land certificates as an instrument to improve SME access to credit requires strong regulatory support, adequate technological infrastructure, and sustainable socialisation and assistance programmes.